GAMING ADDICTION AS A FORM OF CULTURAL DEVIATION (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article explores gaming addiction through the lens of cultural deviation, analyzing it as a complex social phenomenon with deep philosophical implications. By situating excessive gaming within broader cultural, technological, and existential contexts, the paper examines how digital environments reshape individual identity, social norms, and community engagement. Drawing from sociological theories of deviance and philosophical discussions on alienation, escapism, and the virtualization of experience, the study argues that gaming addiction reflects a crisis of meaning in modern society. It critiques the normalization of compulsive digital behavior and considers how such addiction diverges from traditional cultural values, thus functioning as both a symptom and a driver of shifting cultural paradigms. The paper concludes with reflections on ethical responsibility, the role of digital capitalism, and potential avenues for individual and societal resilience.